2011
DOI: 10.1111/j.1365-2745.2011.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil resource availability shapes community trait structure in a species‐rich dipterocarp forest

Abstract: Summary 1.Habitat filtering and limiting similarity have been proposed as two opposing forces structuring community memberships. Community assembly theory proposes habitat filtering as a mechanism restricting community membership according to the ecological strategies of species in a given environment. Limiting similarity posits that some species exclude others that are ecologically similar. 2. We quantified nine ecophysiological and life-history traits for 80 dipterocarp species in the 52-ha Lambir Forest Dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 55 publications
12
89
0
Order By: Relevance
“…The different patterns observed in the two forest types in this study suggest that functional traits may mediate species coexistence according to the limiting factors of a given site: light in temperate rain forests and probably soil moisture in Mediterranean forests. Our findings are in accordance with the results of other studies showing significant relationships between LMA and other leaf traits and patterns of species abundance or occurrence at much coarser spatial scales (Katabuchi et al, 2012;Laurans et al, 2012;Mason et al, 2012). Previous studies have also shown that species' leaf traits in a given community vary significantly across light environments (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…The different patterns observed in the two forest types in this study suggest that functional traits may mediate species coexistence according to the limiting factors of a given site: light in temperate rain forests and probably soil moisture in Mediterranean forests. Our findings are in accordance with the results of other studies showing significant relationships between LMA and other leaf traits and patterns of species abundance or occurrence at much coarser spatial scales (Katabuchi et al, 2012;Laurans et al, 2012;Mason et al, 2012). Previous studies have also shown that species' leaf traits in a given community vary significantly across light environments (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Large-seeded species may preferentially establish in wetter areas which sustain consistent soil moisture such as lowland riparian zones, and small-seeded species may persist in sites with well-drained soils which have a more fluctuating water table. Recent work done in Lambir Hills National Park, Sarawak, Malaysia found an increase in mean seed mass along a soil moisture and fertility gradient with the largest seed masses found on fine clayey soil textures [41], which supports our seed size-sensitivity relationship.…”
Section: Discussionsupporting
confidence: 84%
“…terra firme forests). Our study thus extends on previous research showing the importance of environmental filtering in tropical forests (ter Steege et al 2006;Engelbrecht et al 2007;Kraft, Valencia & Ackerly 2008;Paine et al 2011;Katabuchi et al 2012) to demonstrate that environmental gradients underlie directional shifts in community functional composition across lowland Amazonian forests.…”
Section: S T R O N G E N V I R O N M E N T a L F I L T E R I N G A C supporting
confidence: 68%
“…Kraft, Valencia & Ackerly 2008;Cornwell & Ackerly 2009;Ingram & Shurin 2009). Several recent studies have specifically used functional traits to demonstrate the importance of environmental filtering in determining the assembly of species-rich tropical forests (ter Steege et al 2006;Engelbrecht et al 2007;Kraft, Valencia & Ackerly 2008;Swenson & Enquist 2009;Paine et al 2011;Katabuchi et al 2012). However, these studies included only a few functional traits (ter Steege et al 2006) or species (Engelbrecht et al 2007), or covered relatively small areas (Kraft, Valencia & Ackerlybetter understanding of this issue is critical to improve predictions of the response of community functional composition and associated ecosystem functioning to global change (Lavergne et al 2010;Reu et al 2011).…”
Section: Introductionmentioning
confidence: 99%